2019
DOI: 10.1080/02670844.2019.1587570
|View full text |Cite
|
Sign up to set email alerts
|

The cell culture of titanium alloy surface modifications by micro-powder blasting and co-blast techniques

Abstract: The surface of Ti6Al4V substrate was modified by two ways: micro-powder blasting and co-blast technique. Micro-powder blasting was done using Al 2 O 3 (of three different sizes) or SiC particles. Co-blast technique was done using the same particles co-blasted with hydroxyapatite (HA) particles. The morphology, roughness, deep impact and contact angle were used to characterise the surface modifications. The Ca/P atomic ratio was also determined by co-blast technique. Finally, the biocompatibility of Ti6Al4V sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…The SEM (Scanning Electron Microscope) photographs' surface was much smoother as compared with the surface after sandblasting with an abrasive with sharper edges. Similar results were obtained in zirconium oxide [18] and titanium [19] research. By comparing the results obtained in this study with the results from [20]-where the same nickel-chromium alloy was used, but aluminum oxide was the abrasive-it can be observed that the influence of the processing parameters on the surface condition changes as a result of both the pressure and the abrasive size.…”
Section: Discussionsupporting
confidence: 90%
“…The SEM (Scanning Electron Microscope) photographs' surface was much smoother as compared with the surface after sandblasting with an abrasive with sharper edges. Similar results were obtained in zirconium oxide [18] and titanium [19] research. By comparing the results obtained in this study with the results from [20]-where the same nickel-chromium alloy was used, but aluminum oxide was the abrasive-it can be observed that the influence of the processing parameters on the surface condition changes as a result of both the pressure and the abrasive size.…”
Section: Discussionsupporting
confidence: 90%
“…To promote bone formation, various surface modification techniques such as sandblasting, , acid etching, , chemical treatment, , and anodization , have been employed to form fine or porous structures on Ti surfaces. However, these structures on the Ti surface promote cellular and bacterial growth owing to their specific surface topography and roughness. , The surface composition of Ti plays a pivotal role in determining the competition between host cells and bacteria on the Ti surface.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Therefore, it is imperative to devise a surface design that inhibits bacterial growth while preserving the integrity of host cells to prevent PJI. 2,3 To promote bone formation, various surface modification techniques such as sandblasting, 7,8 acid etching, 9,10 chemical treatment, 11,12 and anodization 13,14 have been employed to form fine or porous structures on Ti surfaces. However, these structures on the Ti surface promote cellular and bacterial growth owing to their specific surface topography and roughness.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Before coating, the substrate surface is often prepared by machining, 51 grinding, 52 polishing, 53 blasting, 54 acid treatment, 55,56 alkaline treatment, 55,56 substrate cleaning, 56 and other processes. 55 Surface coatings of HA and HA composites can enhance biocompatibility, bone tissue response, osteoconductivity, osseointegration, faster implant fixation, and prevent implant slippage.…”
Section: Introductionmentioning
confidence: 99%